On solvable groups, all proper factor groups of which have finite ranks - Tushev, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
This paper deals with finitely generated finitely approximable solvable groups of infinite special rank, all proper normal subgroups of which determine the factor groups of finite special ranks.